Biochemical treatment of poultry manure and buffalo dung to enhance methane generation using lab-scale an-aerobic digester: effect of mesophillic condition on methane generation - Arshad Iqbal Jarwara; Shaheen Aziz; Muhammad Azam Usto; Rasool Bux Mahar; Khadija Qureshi; Imran Nazir Unar; Rizwan Khan; Abdul Sattar Jatoi; Shaukat Mazari; Abdul Karim Shah; Rashid Abro; Zubair Hashmi; et al. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Poultry industry is one of the important growing poultry Industry of Pakistan, the pollution produced due to this causing serious environmental threats such as aquatic life disturbance, air, water and land pollution, pathogen contamination, bad odor, soil contamination and ammonia evaporation. This research study deals with utilization of poultry manure (PM) and buffalo dung (BD) for methane generation and enhance the generation through optimization of substrate mixing ratio and observe the effect of mesophillic condition on methane generation. The PM and BD were biochemically treated by anaerobic digestion. The mixing of P.M and B.D were carried out in ratio 3/1, 1/3 and 1/1 in 500 ml glass bottles acting as bio-reactor. The PM and BD alone were also used in different bioreactor. All the digesters have retention time of 65 days and operated at temperature of 37oC. Each digester distilled water and substrates were used in 1:1 ratio. All the digesters were operated by batch wise process. The generation of biogas from experimental work was maximum from 1:3 of P.M and B.D yield 561 Nml/gm.vs. The methane generation was also maximum in digester containing one part of P.M and three part of buffalo dung the methane generation was also maximum 66 %containing 32 % carbon dioxide. From this study we conclude that biochemical treatment of substrates mixed together in different ratios produces large quantity, quality, higher biodegradability and effective volatile solid removal from substrate.